Universal monsters. Frankenstein - Walsh, Michael (Comic book artist) (Image Comics, 2025)
"This deluxe hardcover tells the shocking creation story of the unforgettable monster in the original film--one body part at a time. Dr. Henry Frankenstein begins his unholy quest to create life by robbing the grave of a decorated police officer to find necessary parts. But little does he know that the corpse has a son who is mourning a father - and that this young boy will forever change Frankenstein's life."--